Adaptação transcultural do instrumento “Occupational Performance History Interview – II” para a língua portuguesa (Brasil) - Gorla, Julia Andreza (Universidade Federal de São Carlos, 2023)
Introduction: The Occupational Performance History Interview – II is an Occupational Therapy instrument based on the Model of Human Occupation (MOHO), which seeks to know the history of the person's occupational performance and, from the information collected, assist in the elaboration of therapeutic goals and intervention planning. Objective: To conduct the cross-cultural adaptation of the instrument Occupational Performance History Interview-II (OPHI-II) Version 2.1, 2004 to the Brazilian Portuguese language. Methodology: based on the Guidelines for the Process of Cross-cultural Adaptation of Self-report Measures and the Report of the ISPOR Task Force for Translation and Cultural Adaptation, the cross-cultural adaptation of OPHI-II was carried out in 6 stages: 1) initial translation; performed by two independent translators; 2) synthesis of translations, with the discussion of divergences and agreements between translators; 3) back-translation, performed by other two independent translators in order to verify the similarity with the original version; 4) committee of specialists, composed of six occupational therapists recognized for their expertise, evaluated the statements in their conceptual, cultural, idiomatic and semantic equivalences; 5) pre-test, with the application of this version and completion of both the scoring scales and the questionnaire on the use of OPHI-II; and 6) final review, in which adjustments were made based on the feedbacks given by the participants. In step 4 (committee of experts), the evaluations were compared, and the agreement index (AI) was calculated for each part of the OPHI-II. For statements with AI lower than 80%, an occupational therapist with extensive knowledge in MOHO and national and international experience was consulted. In the pre-test stage (step 5), seven (n=7) students from the undergraduate course in Occupational Therapy and twelve (n=12) clients, from orthopedics and neurology clinics of the School Health Unit of the Federal University of São Carlos (USE-UFSCar), participated. Each interview was recorded and listened to by another occupational therapist, who also filled out the interview and the scoring scales so that inter-examiner reliability could be analyzed from the calculated AI. Results: Steps 1 to 4 were analyzed according to the MOHO concepts and the original OPHI-II instrument, thus leading to a pre-test version consistent with the foundations of the Model. In the pre-test stage, the AI were calculated, and the feedback given about the use, application and format of the instrument were analyzed for the formulation of the final version of the OPHI-II (Brazil). Conclusion: it is considered that the process of cross-cultural adaptation of OPHI-II for Brazilian use was successful, being available for future research aimed at deepening its psychometric measures and for the application with different clients of Occupational Therapy.
Cross-cultural adaptation of the instrument “Occupational Performance History Interview – II” into Portuguese (Brazil)
Keywords: Adaptação transcultural; Terapia ocupacional; Avaliação; Modelo da ocupação humana; Cross-cultural adaptation; Occupational therapy; Evaluation; Model of human occupation; CIENCIAS DA SAUDE